2002
DOI: 10.1016/s0002-9440(10)62551-5
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Tumor Markers of Pancreatic Cancer using Global Gene Expression Technology

Abstract: Despite several advances in our basic understanding and in the clinical management of pancreatic cancer, virtually all patients who will be diagnosed with pancreatic cancer will die from this disease. The high mortality of pancreatic cancer is predominantly because of diagnosis at an advanced stage of disease and a lack of effective treatments. We used the Gene Logic Inc. BioExpress platform and Affymetrix GeneChip arrays to identify genes differentially expressed in pancreatic cancer. cDNA was prepared from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(166 citation statements)
references
References 35 publications
7
156
2
1
Order By: Relevance
“…For example, osteopontin, a secreted glycoprotein expressed prominently in bone and by lining epithelial cells, was first identified as overexpressed in pancreatic cancers by oligonucleotide microarrays 14 and we have recently found that osteopontin protein levels are significantly elevated in patients with resectable pancreatic adenocarcinoma compared to healthy controls (Po0.001). 15 Other interesting genes identified as overexpressed in the parenchyma of pancreatic cancer and chronic pancreatitis are lactoferrin and fibrinogen.…”
Section: Discussionmentioning
confidence: 95%
“…For example, osteopontin, a secreted glycoprotein expressed prominently in bone and by lining epithelial cells, was first identified as overexpressed in pancreatic cancers by oligonucleotide microarrays 14 and we have recently found that osteopontin protein levels are significantly elevated in patients with resectable pancreatic adenocarcinoma compared to healthy controls (Po0.001). 15 Other interesting genes identified as overexpressed in the parenchyma of pancreatic cancer and chronic pancreatitis are lactoferrin and fibrinogen.…”
Section: Discussionmentioning
confidence: 95%
“…Half of them (26 genes indicated by asterisks in Supplementary Table 1) have been listed as overexpressed genes in pancreatic cancers by microarray analyses in published papers. [13][14][15][16][17][18] This agreement suggested that xenografted specimens are able to serve as a panel for pancreatic cancer.…”
Section: Gene-expression Profiling Of Pancreatic Cancer Xenograftsmentioning
confidence: 94%
“…[13][14][15][16][17][18] In this study, xenografts of clinical specimens orthotopically transplanted into severe combined immunodeficient (SCID) mice 19 were utilized as a panel for gene-expression profiling of pancreatic cancer. Among commonly overexpressed genes in pancreatic cancer xenografts, we further evaluated the adenylate cyclaseassociated protein 1 (CAP1) gene, which encodes an actin monomer-binding protein (reviewed in reference 20 ).…”
mentioning
confidence: 99%
“…Several similar genetic and/or epigenetic abnormalities have also been described in IPMNs including alteration of the K-ras, p53 and STK11/LKB1 genes (Sessa et al, 1994;Sato et al, 2001Sato et al, , 2002. Global gene expression profiles of pancreatic ductal adenocarcinomas and of IPMNs have provided information about candidate molecular markers of these neoplasms as well as providing information as to their tumor biology (Ryu et al, 2001(Ryu et al, , 2002Iacobuzio-Donahue et al, 2002Terris et al, 2002;Logsdon et al, 2003;Sato et al, 2004).…”
Section: Introductionmentioning
confidence: 99%